2012
DOI: 10.3109/10428194.2012.726720
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor receptor-3 expression in mycosis fungoides

Abstract: Here, we have studied vascular endothelial growth factor receptor-3 (VEGFR-3) expression in mycosis fungoides (MF), the most common type of cutaneous T-cell lymphoma (CTCL). Immunohistochemistry revealed that in two-thirds of 34 patients, VEGFR-3 was expressed in situ by both tumor and stromal cells irrespective of the disease stage. The natural VEGFR-3 ligand, VEGF-C, partially protected malignant T-cell lines from growth inhibition by the histone deacetylase inhibitor, suberoylanilide hydroxamic acid (SAHA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
0
24
0
3
Order By: Relevance
“…IL-17A and IL-17F are among cytokines known to promote: (1) angiogenesis and lymphangiogenesis via up-regulation of angiogenic and lymphangiogenic factors 49,50 ; (2) production of prostaglandins such as PGE2 51 ; and (3) up-regulation of inflammatory chemokines and their receptors. 6 Indeed, angiogenic factors such as VEGF and VEGF-C and their receptors are expressed in situ in lesional CTCL skin, 33,52,53 and enhanced angiogenesis correlates with disease progression in CTCL patients. 54,55 Prostaglandin E2 is a growth factor for malignant T cells 56 and Celecoxib, an inhibitor of its production, is able to inhibit tumor growth in vivo in a CTCL xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A and IL-17F are among cytokines known to promote: (1) angiogenesis and lymphangiogenesis via up-regulation of angiogenic and lymphangiogenic factors 49,50 ; (2) production of prostaglandins such as PGE2 51 ; and (3) up-regulation of inflammatory chemokines and their receptors. 6 Indeed, angiogenic factors such as VEGF and VEGF-C and their receptors are expressed in situ in lesional CTCL skin, 33,52,53 and enhanced angiogenesis correlates with disease progression in CTCL patients. 54,55 Prostaglandin E2 is a growth factor for malignant T cells 56 and Celecoxib, an inhibitor of its production, is able to inhibit tumor growth in vivo in a CTCL xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the malignant T cells can trough release of VEGF-A and lymphotoxin α induce enhanced endothelial sprouting in vitro and further trigger fibroblast expression of VEGF-C and angiogenesis in vivo , supporting the concept that the malignant T cells orchestrate profound changes in the tumor microenvironment [133, 135]. Indeed, the malignant T cells strongly impacted skin structure, as well as keratinocyte activation and proliferation, in an organotypic skin model and a xenograft CTCL mouse model [116].…”
Section: The Malignant T Cells Foster Pro-tumorigenic Inflammation Thmentioning
confidence: 90%
“…Accordingly, it has been shown that the presence of cytotoxic CD8 T cells within the CTCL lesions is a positive prognostic factor, and several case reports have evidenced that use of the immunosuppressant cyclosporine in treatment of CTCL accelerates disease progression and large cell transformation [10,29,30]. During the disease progression, the concentration of T H 1 cytokines decreases in contrast to an increased production of T H 2 cytokines and angiogenetic and lymphangiogenetic factors such as VEGF-A and VEGF-C [10,31,32,33,34,35]. This increasing bias towards a T H 2 immune response obstructs an effective cellular immune response and can be framed within the immunoediting hypothesis as a process in which the malignancy transitions from an equilibrium phase to a tumor escape phase.…”
Section: Immunopathogenesismentioning
confidence: 99%